LEGAL RECOGNITION OF METAVERSE PROPERTY RIGHTS AND THE TRANSFER OF VIRTUAL ASSETS IN INDONESIAN PRIVATE LAW - Zico Junius Fernando; Mas Putra Zenno Januarsyah; Firdaus Arifin; Vidyadhara Prawiratama Nugraha; Fardana Kusumah (Indonesia Private Law Review, 2026)
Metaverse has transformed virtual assets into economically valuable objects that challenge conventional concepts of property under Indonesian private law. Although virtual assets such as cryptoassets, non-fungible tokens (NFTs), and metaverse property are widely traded, their legal status remains uncertain, creating ambiguity regarding ownership, transfer, and legal protection. This study examines the normative basis for recognizing virtual assets as objects of property rights within Indonesia's civil law system. Using a normative juridical method with a comparative approach, the study analyzes Indonesian private law alongside developments in England and Wales, Singapore, Japan, and the European Union. The findings demonstrate that virtual assets satisfy the defining characteristics of intangible property, including identifiability, exclusive control, transferability, and economic value, making them capable of recognition as objects of proprietary rights. The study further argues that blockchain-based transfers and smart contracts can operate as legally valid mechanisms for transferring ownership when supported by appropriate legal recognition. To strengthen legal certainty, Indonesia should recognize virtual assets as a distinct category of intangible property, adapt property law to digital transactions, strengthen proprietary remedies, and modernize dispute resolution and cross-border enforcement. These reforms would provide a coherent legal framework for protecting virtual assets and support the development of Indonesia's digital economy.